2016
DOI: 10.2147/ott.s95517
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy plus radiotherapy is superior to chemotherapy following surgical treatment of stage IIIA N2 non-small-cell lung cancer

Abstract: The use of additional radiotherapy for resected stage IIIA N2 non-small-cell lung cancer in the setting of standard adjuvant chemotherapy remains controversial. A comprehensive search (last search updated in March 2015) for relevant studies comparing patients with stage IIIA N2 non-small-cell lung cancer undergoing resection after treatment with adjuvant postoperative chemotherapy alone or adjuvant postoperative chemoradiotherapy (POCRT) was conducted. Hazard ratios (HRs) were extracted from these studies to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Mikell et al ( 18 ) analyzed 2,115 patients with NSCLC in N2 stage who received POCT from 2004 to 2006 in NCDB database, and they concluded that compared with the control group, PORT can improve the 5-years survival rate (39.8 vs. 34.7%, P = 0.048). Lei et al ( 19 ) showed that compared with POCT, PORT combined with POCT was beneficial to OS of IIIA-N2 NSCLC patients, but not to DFS. Our results revealed that for patients with <6 lymph node metastases, PORT combined with POCT therapy has no significant benefit compared with POCT.…”
Section: Discussionmentioning
confidence: 99%
“…Mikell et al ( 18 ) analyzed 2,115 patients with NSCLC in N2 stage who received POCT from 2004 to 2006 in NCDB database, and they concluded that compared with the control group, PORT can improve the 5-years survival rate (39.8 vs. 34.7%, P = 0.048). Lei et al ( 19 ) showed that compared with POCT, PORT combined with POCT was beneficial to OS of IIIA-N2 NSCLC patients, but not to DFS. Our results revealed that for patients with <6 lymph node metastases, PORT combined with POCT therapy has no significant benefit compared with POCT.…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC stage IIIA-N2 disease, neoadjuvant chemotherapy or chemoradiotherapy allows complete resection of the tumor by regressing the stage and decreases the possibility of distant metastasis by providing systemic control in the early period [ 19 , 20 ]. However, a standard multimodal approach could not be defined in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent complete removal of stage IIIA (N2) NSCLC are at risk of local and distant recurrence 7 Adjuvant chemotherapy has been accepted as a part of the standard postoperative treatment of patients with NSCLC, including those with N2 disease. [17][18][19][20] In recent years, with the significant improvement of technology, the simulation, planning and delivery of radiotherapy have been optimized.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Based on several prospective clinical trials that have validated the survival benefit of concurrent chemoradiotherapy over radiotherapy alone 4 or chemotherapy followed by sequential radiotherapy for stage IIIA (N2) NSCLC. 5,6 However, stage IIIA (N2) NSCLC patients have heterogeneous disease presentation, 7 the value of postoperative adjuvant radiotherapy(PORT) for completely resected NSCLC remains controversial, as the effect on survival has been inconclusive. [8][9][10] A secondary analysis of a prospective trial illustrated the benefit of adding PORT in pN2 disease regardless of chemotherapy use, 11 this has been supported by multiple high-volume retrospective investigations.…”
Section: Introductionmentioning
confidence: 99%